Discrimination of responses of corn genotypes to drought through physiological, growth, and yield traits - Santos, Thiago Teixeira; Noqueli, Raphael Augusto das Chagas; Molinari, Hugo Bruno Correa; Kobayashi, Adilson Kenji; Souza Júnior, Manoel Teixeira; Silva, Vivianny Nayse Belo; Ferreira, Thalita Massaro Malheiros; Sousa, Carlos Antônio Ferreira de (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate different traits of four corn (Zea mays) genotypes with contrasting responses to drought and to determine the main traits associated to such responses. The experiment was carried out in a greenhouse. The plants were grown in pots subjected to full irrigation. Drought was imposed to plants at 54 days after sowing and kept constant for 12 consecutive days; however, a group of plants remained under full irrigation. Traits related to leaf gas exchange, photochemical apparatus, growth, and yield were assessed, and data were subjected to hierarchical agglomerative clustering and principal component analysis. DKB 390 distinguishes from the other genotypes for growth and yield traits, while 2B-707 and DKB 390 discriminate from 'BRS 1030' and 'BRS 1010' for physiological traits. Ear length, kernel number per ear, above-ground dry matter, shoot dry matter, and plant height are the most important growth and yield traits to discriminate genotype-dependent drought tolerance. Among the physiological traits, the most important are: chlorophyll content, absorptivity, leaf temperature, maximum fluorescence in the dark-adapted state, minimum fluorescence in the dark-adapted state, water-use efficiency, and intercellular CO2 concentration.